Valid cardiac biochemical markers. Part II - N. G. Gumanova; M. V. Klimushina; N. L. Bogdanova; O. V. Stefanyuk; V. A. Metelskaya (Кардиоваскулярная терапия и профилактика)
This publication is a continuation of the review of cardiac biomarkers approved by the Food and Drug Administration (USA), including analysis of prospective research, clinical trials and meta-analyses. In the first part, along with data on general concepts, definitions and classification of biomarkers, diagnostic and prognostic biomarkers of cardiovascular diseases associated with atherosclerosis are studied. In the second part of the review, valid cardiac biomarkers and their diagnostic value in clinical practice are considered.